TAXONOMICAL STUDIES OF BIOACTIVE BACTERIAL ISOLATE-MSB-6 - M D A G CHANDRA SEKHAR; CH. MURALI MOHAN (International Journal of Pharma and Bio Sciences, 2014)
In order to identify the resulted bioactive strain MSB-6 from primary and secondary screening of marine soil samples, various morphological, physiological and biochemical tests are performed. Further confirmation is done by the 16S rRNA gene analysis. The reports confirmed strain MSB-6 as Pseudomonas fluorescens and it is deposited to Gene Bank with the accession number KC852045. It is mesophilic, alkaliphilic and moderately salt tolerant in nature. It ferments dextrose, galactose, inulin, xylose, mannose, melibiose, L-arabinose and showed positive results to citrate utilization test, cytrochrome oxidase test, catalase test, gelatin hydrolysis, casein hydrolysis and nitrate reduction. Altogether, the results once again proved that the natural marine environment is also good source for isolation of novel varieties of antagonistic bacteria.The culture conditions are optimizing for the production of antimicrobial metabolites by MSB-6 bacteria. The metabolite production is started after 24 h of incubation and reached its maximum levels after 48 h and decreased gradually. The pH is adjusted to 7.0 and temperature to 370C supported the production of antimicrobial metabolites. The best proved carbon source was dextrose respectively as basal medium.